Different precipitation patterns across tropical South America during Heinrich and Dansgaard-Oeschger stadials. (1st December 2017) - Zhang, Yancheng; Chiessi, Cristiano M.; Mulitza, Stefan; Sawakuchi, André O.; Häggi, Christoph; Zabel, Matthias; Portilho-Ramos, Rodrigo C.; Schefuß, Enno; Crivellari, Stefano; Wefer, Gerold
Abstract: Detailed knowledge about tropical South American precipitation patterns during Heinrich (H) and Dansgaard-Oeschger (DO) stadials provides relevant insights into the possible evolution of Amazonian hydroclimate under future climate change. Sediment core GeoB16224-1 (ca. 7°N), raised from a site in the continental slope off French Guiana in western equatorial Atlantic under the influence of the Amazon River discharge, documents the impacts of H and DO stadials on both inorganic (i.e., Fe/Ca record) and organic (i.e., alkenone C37 concentration and C37 /C38 ratio) geochemistry between 41 and 13 ka BP. Our results show millennial-scale covariations of increased Fe/Ca values with decreased C37 concentration and C37 /C38 ratios during H and DO stadials. Comparing our high temporal resolution data with previously published records from ca. 17°N to 4°S, we are able to differentiate the influence of H and DO stadials upon tropical South American precipitation. We find that records under the influence of the South American summer monsoon (e.g., western Amazon) and the northern edge of the Intertropical Convergence Zone (ITCZ) (e.g., northernmost South America) exhibit strong climate shifts during both H and DO stadials, but regions under the influence of the southern edge of the ITCZ (e.g., northeastern Brazil) experience a weaker reaction during DO stadials than during H stadials. Highlights: Weakened AMOC led to enhanced Andean sediment input to western tropical Atlantic. ITCZ shift caused predominance of coastal haptophytes in western tropical Atlantic. We disentangle tropical South American precipitation pattern over H and DO stadials. Rainfall in NE Brazil underwent a weaker reaction to DO stadials than to H stadials.